Gaps in Preparedness for Independent Medical Practice Among Indonesian Medical Graduates: A Cross-Sectional Study - Muhammad Idham Rahman; Rachmadya Nur Hidayah; Gandes Retno Rahayu (Education in Medicine Journal, 2026)
Ensuring that medical graduates are adequately prepared for independent medical practice is a fundamental responsibility of medical faculties worldwide. However, recent literature indicates that many new medical graduates feel insufficiently prepared to manage complex clinical problems despite completing their training. This national cross-sectional study assessed the preparedness of Indonesian medical graduates for independent medical practice. A questionnaire adapted from the Indonesian Medical Competency Standards measured preparedness across six domains, including clinical skills, patient management, practical procedures and skills, communication and teamwork, clinical guidelines and protocols, and personal development and well-being. Responses were ratedon a six-point Likert scale and collected electronically via snowball sampling. A total of 270 recent graduates from 50 medical faculties across Indonesia completed the survey (response rate: 17.5%). Graduates reported a high overall level of preparedness (mean 5.26 ± 0.56 out of 6). Respondents from outside Java and those trained in lower-tier hospitals (Types C and D) demonstrated significantlyhigher preparedness in the clinical and personal development domains (p = 0.011 and p = 0.017, respectively). Despite these favourable findings, preparedness was lowest for managing complex cases involving cognitive, psychological, and circulatory disorders, suggesting a potential gap in clinical exposure during training. Indonesia’s medical education and internship programmes appear effective in preparing graduates for independent practice. Nevertheless, enhanced clinical exposure and structured supervision, especially in complex case management, is essential for enhancing graduates’ competence and confidence.